PENGEMBANGAN MEDIA E-LKPD UNTUK MENINGKATKAN ARGUMENTATION SKILLS SISWA SMP DALAM PEMBELAJARAN IPA - Estian Ega Avianti; Supeno Supeno; Zainur Rasyid Ridho (ScienceEdu, 2023)
The essence of science learning is process that requires students not only to memorize a concept, but to fully understand the concept of every context in daily life so they have a logical thinking. Based on the results of PISA 2018, Indonesian students are still at level 1 and 2. They have not been able to provide explanations about scientific phenomena, events and processes. These results shows that the quality of student’s argumentation is still at low level. To improve the ability of scientific analysis, argumentation skills is needed to improve the argument of student’s. Argumentation skills has a main role in analytical knowledge. The argumentation learning can involve students in presenting valid evidence, data, and theories that support their opinion of a problem they encountered. The method used in this study is a quantitative method. This study aims to determine the validity, practicality, and effectiveness of the development of E-LKPD to improve the argumentation skills of junior high school students in science learning. The validation results of ELKPD to improve the argumentation skills of junior high school students in science learning by 88.6%, practicality test results by 89% and effectiveness test results that using n-gain by 0.67.